Complementary and alternative medicine use among patients with psoriasis. Issue 5 (25th June 2014) - Damevska, Katerina; Neloska, Lence; Nikolovska, Suzana; Gocev, Gorgi; Duma, Silvia
Abstract Despite the growing attention on safety and efficacy of conventional treatments, there is little information available on complementary and alternative medicine (CAM) used in psoriasis. In order to collect comprehensive information on CAM use, we conducted a face‐to‐face interview with 122 patients with psoriasis. All unconventional treatments for psoriasis used in the last 12 months were recorded. Fifty‐seven patients (46.7%) used one of the CAM methods in the previous year, including topical and systemic antipsoriatics, dietary supplements, and diet. Forty‐one different nonconventional topical treatments were used. Seven patients (5.7%) took nonconventional systemic medication, and 15.5% used dietary supplements. There were three patients who reported current adherence to a diet as treatment of psoriasis. Clinicians are often not informed that their patients are using complementary therapies. CAM may offer benefits as well as risks to patients with psoriasis. It is important to remind patient to report all ongoing and past topical and systemic treatments. The use of medications with unknown composition, efficiency, and safety should be discouraged.